The increase of working efficiency of scraper elevators with centrifugal unloading - Бурлака, О. А.; Яхін, С. В. (Scientific Progress & Innovations, 2018)
When transporting grain, the return fall and, respectively, partial crushing of grain by scrapers, a chain and asterisks of an elevator are observed. It is because of detected imperfection of an elevator’s head design combined with a tension device The correction of a trajectory of a grain flow is carried out by a cover of an upper part of an elevator. If the time of the movement of grain on an elevator scraper surface is equal or smaller than the time of rotation of a scraper when passing a zone of unloading, then we have a high probability of hit of layers of a grain flow in necessary limits, at the same time centrifugal unloading is successfully. If the trajectory of grain layers gets to a lower zone, then there is a possibility of grain entering in a single part of a scraper elevator that is, the return rash, circular circulation of grain in an elevator casing, is formed. Such phenomenon is negative as it involves additional power costs of transportation; increases crushing and compression damage of grain weight, accelerates wear of operating parts of the grain transport system of the combine. The next part of the research, devoted to the ways of improvement of centrifugal unloading in a scraper elevator, is optimization of size of the sector of unloading. For the solution of such task we have conducted a number of researches by means of special experimental installation. It is possible to change the sector of a zone of unloading by means of change of height of unloading zone. Speed of transportation of grain was different with the change of turns of a power shaft with an asterisk to a chain occasion with scrapers. According to the result of the experiment measurement of power parameters of grain transportation by a scraper elevator is taken, at the same time it is found out that reduction of circular circulation in an elevator from 7-10% to 2-3% of the general supply of grain gives the chance to save 0,075-0,085 kW of power costs of transportation with a productivity of elevator of 5-5,5 kg/s. To eliminate this drawback, it is proposed to install an of the additional directing casing in the upper part of the scraper elevator of the additional directing casing . To eliminate this drawback, it is proposed to install an additional directing body in the upper part of the scraper elevator.